Demobilization and Remobilization of German and Lithuanian Paramilitaries after the First World War. (January 2015) - Balkelis, Tomas
This article explores the dynamic relationship between demobilization and remobilization in Lithuania after 1918. Focusing on the formation of Lithuanian and German paramilitaries and their military roles in the postwar conflict, the article argues that their emergence was grounded in their experiences of the Russian revolution and demobilization. War veterans formed the nucleus of both groups but they were joined by new volunteers who saw the postwar conflict as an opportunity to fulfil their nationalist, anti-Bolshevik or revanchist aspirations. The paramilitaries played significant roles in state- and nation-building in the Baltic region.